YOUTUBE VLOG-BASED POP SONG LEARNING: ANALYSIS OF CULTURAL ARTS (MUSIC) LEARNING IN JUNIOR HIGH SCHOOL - Agustina Ratri -Probosini; Hana Permata Heldisari; Hosea Agave Putra (Sean Institute, 2023)
The Covid-19 pandemic that has hit Indonesia has resulted in changes in the implementation of learning. The change from face-to-face learning to online learning has resulted in problems. Problems also occur in music learning at SMP Negeri 1 Yogyakarta. The implementation of learning is not effective due to two things, firstly during the learning process there is a network disruption so that not all students can follow the learning process smoothly and secondly the use of the Google Meeting application is not suitable for learning cultural arts. The purpose of this study is to describe the application of Youtube vlog-based pop song learning at SMP Negeri 1 Yogyakarta.This research uses qualitative descriptive methods, conducted to describe, and understand the data objects studied in depth. The data source is a primary, and secondary data source. Data collection techniques in this study are observation, interviews, literature studies, and documentation. The data analysis used includes data reduction, data presentation, and data verification. Vlog-based learning or using videos can be used as an effective learning medium to carry out the learning process. Youtube vlogs as a medium used during online learning can increase productivity, and make it easier for teachers, as well as students to convey and access music learning materials well, especially pop song material.